Quality of doctor-patient communication and likelihood of adherence to treatment protocols an explanatory study of moderators of communication effect - Bernadas, Jan Michael Alexandre C., 1984-; David, Clarissa (2012.)
"Using quasi-experimental strategy and survey technique, this three-phased study hypothesizes the effect of quality of doctor-patient communication on adherence to treatment protocols among selected out- and private patients diagnosed with hypertension. Based on modified versions of Physician-Patient Relationship Inventory, Adherence Self-efficacy Scale, and Trust in Physician Scale, this study also examines how adherence self-efficacy and interpersonal trust moderate the hypothesized effect. Analysis of variance reveals that quality of doctor-patient communication has significant effect on adherence in the second phase only. Furthermore, univariate general linear model reveals that adherence self-efficacy and interpersonal trust do not moderate the effect of quality of doctor-patient communication on adherence to treatment protocols in the second phase. Implications on interpersonal communication theory, quasi-experimental strategy, survey technique, patient and support group education, and curriculum development in medical schools are discussed."
Vita.
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Keywords: Communication in medicine; Interpersonal communication; Physician and patient -- Philippines